Analisis Pendapatan Usaha Peternakan Bebek Pedaging Di Probolinggo Jawa Timur - Ahmad Fawaid; Saladin Ghalib; Irwansyah Irwansyah (Universitas Lambung Mangkurat, 2018)
This study aims to: To know the comparative income of Duck Breeding farm business in Probolinggo East Java based on business scale. This study is a descriptive type with a comparative approach. The study was conducted at three (3) farm located in Probolinggo East Java Province which consists of Livestock Razak, CV. Detail Group, and UD Barokah. The data collection is done by interview, and literature and documents. The results showed that: Comparative Revenue of broiler duck business in Probolinggo East Java shows that Razak Ranch has a liquidity ratio of 1.80, solvency ratio of 1.39 and profitability ratio of 14.9%. UD Barokah has a liquidity ratio of 2, solvency ratio of 1.65 and profitability ratio of 23.26%. CV Detail Group has a liquidity ratio of 1.94, a solvency ratio of 1.50 and a profitability ratio of 23.26%. The results show that the income of a farm is not only determined by the scale of business, but also by the management system. Keywords: Revenue, Business Scale, Livestock, duck Broiler